Next generation sequencing to identify new genetic causes of familial craniosynostosis - Hashimoto, A (2017)
Craniosynostosis, the premature fusion of one or more cranial sutures, is one of the most common craniofacial abnormalities. There is considerable genetic heterogeneity and the underlying pathophysiological mechanisms are diverse, occurring at multiple stages of cranial suture biogenesis. A genetic diagnosis, currently made in ~25% of cases, is an important aspect of the multidisciplinary approach to clinical management and genetic counselling. The aim of this thesis is to identify novel genetic causes of craniosynostosis in unsolved familial cases. Four families were selected and investigated using a combination of next generation sequencing and copy number analysis. Candidate changes were followed up through segregation and functional analysis to determine if they were causal. The most convincing finding was a homozygous deletion identified in the 5′ UTR (untranslated region) of dehydrogenase/reductase 3 (DHRS3) in a consanguineous family with syndromic coronal synostosis. This deletion was shown to lead to loss of DHRS3 activity and an increase of all-trans-retinoic acid (ATRA), a known teratogen that had previously been deduced to contribute to craniosynostosis. These findings are consistent with a novel embryopathy caused by excess ATRA, leading to skeletal and cardiac defects. In a second large family with syndromic metopic synostosis, a nonsynonymous variant in HIST1H2AD, encoding one of the canonical histone H2A components of the nucleosome, was identified. Although a link between histone mutation and craniosynostosis is unknown, we speculated that this variant could perturb gene expression during development of the metopic suture. To gain support for causality, two approaches were undertaken; 1. Search for additional patients with a variant in H2A genes including resequencing in a large cohort of patients with craniosynostosis. 2. Creation of Hist1h2ad mutant Embryonic Stem cells using CRISPR/CAS9; Generation of the mouse model is ongoing. Chromosomal rearrangements can be pathogenic through altering the topological associated domain (TAD) structure. A de novo tandem duplication on chromosome 4 including FGF5 and C4orf22 was identified in a third family (affected mother and daughter) with multiple suture synostosis. The duplication overlaps TAD boundaries, leading to the hypothesis that this may induce mis-expression of genes in or near the duplication. Gene expression analysis was undertaken. To investigate this further, work using Capture-C, a technique used to discover local chromatin structure and interactions, is ongoing. In summary, I have identified a new craniosynostosis disease gene, DHRS3, suggesting an additional aetiology in osteogenesis of the cranial suture caused by disruption of retinoic metabolism. In addition, two loci, HIST1H2AD and FGF5/C4orf22 duplication, are plausible candidates for craniosynostosis with possible roles in disturbing neural crest development and RAS/MAPK signalling, respectively. Finally, this work illustrates a combined genomic technology approach to resolve difficult cases that may be applicable apply to other diseases in which a genetic cause is suspected.